Product Development Strategy and Non-Financial Performance of Kenya’s Travel Agencies - Maina, Tracy Wangechi; Kibe, Lucy; Kembu, Appolonius (Acta Universitatis Danubius. Œconomica, 2025)
Objectives: This study analyzes the influence of product development strategy on the non-financial performance of travel agencies in Nairobi, Kenya. The travel sector significantly contributes to Kenya’s growth and development; however, it faces challenges in developing and adapting products to the market’s ever-evolving needs. Prior work: While several studies have been conducted on the tourism industry in Kenya, the researchers are aware of no explicit studies that assess travel firms registered with the Kenya Association of Travel Agencies. Approach: The researchers utilized a descriptive cross-sectional design to examine the influence of product development strategy on the non-financial performance of travel agencies in Nairobi, Kenya. The study was anchored on pragmatism to collect both qualitative and quantitative data from the respondents. Results: Product development strategy (Coeff = 0.66, p-value = .00) has a statistically significant influence on the non-financial performance of travel agencies. Implications: This research offers insights policymakers and tourism practitioners can use to formulate and execute strategies that foster the growth, development, and sustainability of travel agencies. Value: The study extends the strategic management literature by examining product development strategy through the lens of the resource-based view and the non-financial performance of travel agencies.